Prenatal Depression and Infant Temperament: The Moderating Role of Placental Gene Expression. (5th October 2017) - Zhang, Wei; Finik, Jackie; Dana, Kathryn; Glover, Vivette; Ham, Jacob; Nomura, Yoko
Abstract : Prior research has demonstrated the link between maternal depression during pregnancy (i.e., prenatal depression) and increased neurodevelopmental dysregulation in offspring. However, little is known about the roles of key hypothalamic–pituitary axis regulatory genes in the placenta modulating this association. This study will examine whether placental gene expression levels of 11 β ‐hydroxysteroid dehydrogenase type 2 ( HSD11B2 ), glucocorticoid receptor ( NR3C1 ), and mineralocorticoid receptor ( NR3C2 ) can help elucidate the underlying mechanisms linking prenatal depression to infant temperament, particularly in infants with high negativity and low emotion regulation. Stored placenta tissues ( N  = 153) were used to quantify messenger ribonucleic acid levels of HSD11B2, NR3C1, and NR3C2 . Assessments of prenatal depression and infant temperament at 6 months of age were ascertained via maternal report. Results found that prenatal depression was associated with increased Negative Affectivity ( p  < .05) after controlling for postnatal depression and psychosocial characteristics. Furthermore, the association between prenatal depression and Negative Affectivity was moderated by gene expression levels of HSD11B2, NR3C1, and NR3C2 such that greater gene expression significantly lessened the association between prenatal depression and Negative Affectivity. Our findings suggest that individual differences in placental gene expression may be used as an early marker of susceptibility or resilience to prenatal adversity.